FINANCING TOURISTIC RESOURCES: A COMPREHENSIVE ANALYSIS OF SUSTAINABLE TOURISM FUNDING MODELS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This paper explores the financing mechanisms involved in the development and sustainability of tourism resources, with a particular focus on funding models that balance economic growth with environmental and social responsibility. Through a qualitative approach that includes literature reviews and case study analyses, the paper highlights various models for financing tourism development, such as public financing, private investment, public-private partnerships (PPPs), and communitybased funding. It also examines sustainable financing methods, including eco-tourism investments and green bonds. By analyzing real-world examples and theoretical models, the paper aims to provide a comprehensive framework for tourism financing that can help policymakers, investors, and communities address the challenges and opportunities in tourism development.